The Effect of Problem-Based Learning Model Assisted by PhET Simulations on Students’ Physics Problem-Solving Abilities - Liana, Liana; Kosim, Kosim; Taufik, Muhammad; Hikmawati , Hikmawati (Department of Physics Education, Universitas Mataram, 2023)
This study aims to examine the effect of problem-based learning model assisted by PhET simulations on students' physics problem solving ability. This research is Quasi Experimental with non-equivalent control group design. The population of this study were all students of class XI IPA SMAN 4 Mataram with sampling technique using purposive sampling technique, because there were four classes XI IPA, so it was determined that class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. Based on the results of the study, the average value of physics problem solving ability of students in the experimental class was 45.09, while the average value of problem-solving ability of the control class was 39.61. Data Problem solving ability of both classes are normally distributed. Based on the results of the data homogeneity test, the problem-solving ability data are both homogeneous. Problem solving ability data was analyzed using the polled variance t-test and obtained a t_count of 2.24. The t-table value for problem solving ability data is 2.00 at a significant level of 5%. The value of t_count is greater than t_table, meaning that there is an effect of problem-based learning model assisted by PhET simulations on physics problem solving ability of students.